Diminished Expression of P-glycoprotein Using Focused Ultrasound Is Associated With JNK-Dependent Signaling Pathway in Cerebral Blood Vessels - Choi, HyoJin; Lee, Eun-Hee; Han, Mun; An, Sang-Hyun; Park, Juyoung (Frontiers in Neuroscience, 2019)
MRI-guided focused ultrasound (MRgFUS) combined with microbubbles (MBs) is a promising technology that can facilitate drug delivery through a temporarily disrupted blood-brain barrier (BBB) and induce the down-regulation of P-glycoprotein (P-gp) expression on the blood vessels. Despite the increasing evidence regarding the down-regulation of P-gp expression after MRgFUS BBB disruption (BBBD), its underlying molecular events remain unclear. The aim of this study was to evaluate the underlying mechanism of FUS BBBD-mediated P-gp down-regulation. While our results showed down-regulation of P-gp at 24 h post-BBBD in transcriptional and translational levels, restoration to the normal expression appeared at different time points for transcriptional (72 h) and translational (120 h) levels. In addition, the signaling molecule, JNK, was significantly activated in the cerebral blood vessels at 24h post-BBBD. Although P-gp levels were significantly decreased, the expression levels of proteins involved in the integrity of blood vessels, such as Glut1, ZO-1 and occludin, were not decreased at 24 h post-BBBD. Our study suggests that the JNK signaling pathway is involved in the regulation of FUS-induced P-gp expression, without affecting vessel integrity, and a detailed regulatory mechanism can provide the basis for clinical application of FUS to the treatment of neurological disease.